2006
DOI: 10.1002/cne.20917
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the second cervical dorsal root ganglion to the cochlear nucleus in rats

Abstract: Physiological, anatomical, and clinical data have demonstrated interactions between somatosensory and auditory brainstem structures. Spinal nerve projections influence auditory responses, although the nature of the pathway(s) is not known. To address this issue, we injected biotinylated dextran amine into the cochlear nucleus or dorsal root ganglion (DRG) at the second cervical segment (C2). Cochlear nucleus injections retrogradely labeled small ganglion cells in C2 DRG. C2 DRG injections produced anterograde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 76 publications
0
64
0
2
Order By: Relevance
“…The existence of CST is supported by several animal studies, which have found connections between the cervical somatosensory system and the cochlear nuclei (CN) (3,4). Cervical somatosensory information is conveyed by afferent fibers, the cell bodies of which are located in the dorsal root ganglia or the trigeminal ganglion, to the brain.…”
Section: Main Outcome Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…The existence of CST is supported by several animal studies, which have found connections between the cervical somatosensory system and the cochlear nuclei (CN) (3,4). Cervical somatosensory information is conveyed by afferent fibers, the cell bodies of which are located in the dorsal root ganglia or the trigeminal ganglion, to the brain.…”
Section: Main Outcome Measuresmentioning
confidence: 98%
“…Within the group of patients suffering from chronic subjective nonpulsatile tinnitus, a subgroup can be defined where the tinnitus is related to the somatosensory system of the cervical spine (2). This type of tinnitus is named cervicogenic somatic tinnitus (CST).The existence of CST is supported by several animal studies, which have found connections between the cervical somatosensory system and the cochlear nuclei (CN) (3,4). Cervical somatosensory information is conveyed by afferent fibers, the cell bodies of which are located in the dorsal root ganglia or the trigeminal ganglion, to the brain.…”
mentioning
confidence: 97%
“…1). Specific sensory projection neurons to the CN originate in the trigeminal ganglion and the spinal trigeminal nucleus (Sp5) (Haenggeli, et al, 2005, Shore, et al, 2000, Zhou and Shore, 2004), dorsal root ganglion and dorsal column nuclei (Itoh, et al, 1987, Zeng, et al, 2011, Zhan, et al, 2006, Zhou and Shore, 2004), saccule and vestibular nucleus (Barker, et al, 2012, Bukowska, 2002, Burian and Gstoettner, 1988). Most of the projections from non-auditory sensory ganglia and brainstem nuclei terminate in the CN granule cell domain (GCD), but some of them end in magnocellular CN regions (Gomez-Nieto and Rubio, 2011).…”
Section: Multisensory Integration In the Cochlear Nucleusmentioning
confidence: 99%
“…VGLUT1 expression is intense in the core region of VCN and deep DCN where ANFs terminate on principal projection neurons, while VGLUT2 expression is stronger in the granule cell domain (GCD), which receives most of the non-auditory inputs to the CN (Haenggeli et al, 2005; Ohlrogge et al, 2001; Wright and Ryugo, 1996; Zhan et al, 2006; Zhan and Ryugo, 2007; Zhou et al, 2007; Zhou and Shore, 2004; 2006b). Furthermore, terminal endings originating in the spinal trigeminal nucleus (Sp5), cuneate nucleus and lateral reticular nucleus co-label with VGLUT2 and not VGLUT1 (Cui and Shore, 2008; Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%